Asymmetric Decentralization in Indonesia: Monarchical Legacy and Sultanate Succession in Yogyakarta - Sulaiman, King Faisal; Nasrullah, Nasrullah; Ahmad, Ahmad; Fathi, Muhammad; Musa, Nurhafilah (SASI, 2026)
Introduction: This study analyzes the legitimacy of the Crown Princess’s appointment in Yogyakarta through the Sabda Raja decree and its alignment with Paugeran Adat, the customary constitutional foundation of the Yogyakarta monarchy. Purposes of the Research: It also examines the broader implications of this appointment for the gubernatorial position in the Special Region of Yogyakarta and offers recommendations for future succession models. Methods of the Research: This research employs a normative legal approach, comprising three stages: a literature review of primary and secondary legal materials, conceptual and comparative analysis, and the formulation of conclusions and recommendations. Results of the Research: The findings highlight Yogyakarta's distinctive asymmetric decentralization, particularly its hereditary gubernatorial succession. The Crown Princess's appointment as Heir contravenes Paugeran Adat, which traditionally forbids female Sultans. To override this customary barrier, the Sultan issued the Dawuh Raja (King's Decree), yet this move has generated substantial controversy. Adding to this complexity, the Constitutional Court's ruling affirms the Sultan's prerogative without explicitly adjudicating gender qualifications, thereby leaving a legal vacuum that fuels the ongoing dispute. To address this, the study recommends revising the Special Autonomy Law to align legal provisions with local constitutional customs, ensuring future successions are both legally sound and culturally coheren.